The Influence of Brand Image, Brand Awareness, and Labeling Halal Against the Decision to Purchase Sarimi Instant Noodle Products at Alfamidi Jeruk Raya, South Jakarta - Chaerillya Chaerillya; Resti Hardini; Kumba Digdowiseiso (Jurnal Syntax Admiration, 2023)
This study aims to analyze the effect of brand image, brand awareness, and halal labeling on purchasing decisions for Sarimi instant noodle products at Alfamidi Jeruk Raya, South Jakarta. The population in this study were customers who bought Sarimi instant noodle products at Alfamidi Jeruk Raya, South Jakarta. The sample used in the study was 96 people. Collecting data in this study using a questionnaire. This study uses multiple linear regression analysis techniques to test the independent variables on the dependent variable. The results of this study found that brand image and brand awareness had a positive and significant effect on purchasing decisions, however, halal labeling had a positive but not significant effect on purchasing decisions for Sarimi instant noodle products at Alfamidi Jeruk Raya, South Jakarta.